Innovative Approach: Reducing Hypertension in the Elderly through Ergonomic Gymnastics and Murottal Al-Quran Surah Ar-Rahman - Rhameyana, Dian; Nurjannah (Sahabat Publikasi Kuu, 2025)
Hypertension is one of the degenerative diseases that is often experienced by the elderly and can cause serious complications such as stroke and heart disease. Non-pharmacological treatments such as ergonomic gymnastics and spiritual therapy through murottal Al-Qur'an can be an alternative to help lower blood pressure. This study aims to determine the effect of the combination of ergonomic gymnastics and murottal Surah Ar-Rahman on lowering blood pressure in the elderly with hypertension. The research design used was one group pre-posttest design. The sample consisted of 36 elderly with hypertension. The intervention carried out was ergonomic gymnastics while listening to murottal Surah Ar-Rahman for 30 minutes, three times a week for four weeks (January 9-February 9, 2025). Blood pressure measurements were taken before and after the intervention. The results showed a significant decrease in systolic and diastolic blood pressure (p <0.000). The combination of gymnastics and murottal is effective in lowering blood pressure in elderly hypertensive patients. This intervention can be used as a holistic and religious complementary therapy option in the care of the elderly with hypertension